Antibacterial activity of five Indonesian medicinal plants and the isolation of compounds from Plectranthus scutellarioides - Senda Kartika Rakainsa, Khoirun Nisa, Takuya Ito, Hiroyuki Morita (Journal of Applied Pharmaceutical Science, 2024)
The purpose of this study is to investigate the antibacterial properties of five Indonesian medicinal plant extracts, namely Physalis angulata, Loranthus parasiticus, Plectranthus scutellarioides, Cyperus rotundus, and Terminalia catappa. The isolation of compounds from P. scutellarioides against pathogenic bacteria was also investigated. The assessment of the antibacterial activity of the extracts was conducted using the microdilution-3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyltetrazolium bromide method against Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli). The plant extract with the highest antibacterial activity was further purified using various chromatographic assays to isolate bioactive compounds. High Resolution-Electron Ionization Mass Spectroscopy/Electrospray Ionization Mass Spectroscopy (HR-ESIMS/EIMS) and Nuclear Magnetic Resonance (NMR) spectrometers were used to elucidate the structure of isolated compounds. Among all the plants tested, P. scutellarioides showed the strongest antibacterial activity against S. aureus [minimum inhibitory concentration (MIC 100 μg/ml)] and B. subtilis (MIC 200 μg/ml). Three compounds were isolated from P. scutellarioides including an abietane diterpene, 2,16-diacetoxy-6,11,12,14,17-pentahydroxy-abieta-5,8,11,13- tetraene-7-one (1), 5,6,7,3′,4′,5′-hexamethoxy flavone (2), and 5,6,7,8,3′,4′,5′-heptamethoxy flavone (3). Compounds 2 and 3 were recognized to be first isolated from this plant. Compound 1 exerted antibacterial activity against S. aureus with a MIC value of 60 μM, but was inactive against B. subtilis and E. coli (MIC > 200 μM). Compounds 2 and 3 were inactive against S. aureus, B. subtilis, and E. coli (MIC > 200 μM).
Keywords: Antibacterial activity, Indonesian medicinal plants, isolation, Plectranthus scutellarioides